(untitled) (Journal of Atomic and Molecular Sciences, 2018)
Non-relativistic energies of 1s^22s and 1s^2np (≤ 9) states for Cu^26+ ion are calculated by using the full-core plus correlation method. For 1s^22s and 1s^22p states, relative discrepancies between our results and high precision results of Yan et al. are within 0.1 ppm. By taking account of the first-order corrections to the energy from relativistic and mass-polarization effects, the higher-order relativistic contribution and QED correction to the energy are estimated under a hydrogen-like approximation. The transition energies, wavelengths and oscillator strengths for the 1s^22s-1s^2np transitions of the ion are calculated. The results obtained by the three forms are in good agreement with each other.